Take a ball of string : 16 beautiful projects for your home - Schlee, Jemima (Schlee, Jemima. Take a--., 2015)
Everyone has at least one long-forgotten ball of string lurking at the back of a drawer. Take a Ball of String shows us how to transform this everyday mundane item into an array of exciting makes. The pleasingly tactile nature of string makes it perfect for creating some crafty treasures. From rustic garden twine to soft cotton braid, these eye-catching projects will inspire you to get knitting, crocheting, coiling and knotting. The 16 projects fall into four main sections: Kitchen, Bathroom, Porch and Study. All the basic techniques and know-how are explained, with clear step-by-step instructions and pictures.